2019
DOI: 10.1111/rda.13483
|View full text |Cite
|
Sign up to set email alerts
|

CK1 inhibitor affects in vitro maturation and developmental competence of bovine oocytes

Abstract: The objectives of present study were to evaluate the effect of casein kinase 1 (CK1) inhibition D4476 on in vitro maturation (IVM) and developmental competence of bovine oocytes. The cumulus oocyte complexes (COCs) were cultured in maturation medium with D4476 (0, 2, 5, 10, 20 μM) for 24 hr. After IVM and in vitro fertilization, through expansion average scores of cumulus cells (CCs), oocyte maturation efficiency, cleavage rate and blastocyst rate of zygote, we found 5 μM D4476 could increase the development p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Moreover, the organization of linear molecules of hyaluronan is mediated by TNFAIP6 [33] and PTX-3 [34]. It has been reported that these factors were involved in the quality of oocyte maturation [35]. In the present study, supplementation of the IVM medium with 10 µg/mL TA significantly increased the cumulus expansion of porcine COCs and the expression of genes related to cumulus expansion in cumulus cells.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, the organization of linear molecules of hyaluronan is mediated by TNFAIP6 [33] and PTX-3 [34]. It has been reported that these factors were involved in the quality of oocyte maturation [35]. In the present study, supplementation of the IVM medium with 10 µg/mL TA significantly increased the cumulus expansion of porcine COCs and the expression of genes related to cumulus expansion in cumulus cells.…”
Section: Discussionsupporting
confidence: 57%
“…Using GAPDH as an internal reference, the relative expression levels were calculated by the 2 −∆∆Ct method. Total RNA extraction, reverse transcription and real-time PCR were reference to a report [ 32 ]. Related primers are shown in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Approximately one thousand COCs were collected. The full expansion of CCs was recorded as three points; the partial expansion was recorded as two points; and no extension was recorded as one point (Shi et al, 2019).…”
Section: Methodsmentioning
confidence: 99%